P207 Clinical outcome of patients with Ulcerative colitis after anti-TNF discontinuation - 10 years follow up. (27th May 2021) - Johnsen, K M; Mona, D G; Florholmen, J; Goll, R
Abstract: Background: Biological therapy for ulcerative colitis (UC) such as anti-TNF have shown high efficacy in achieving remission. There is a lack of information about the long-term outcomes after biologic withdrawal and validated clinical, immunologic, genetic or laboratory markers that can predict outcome after withdrawal accurately. The aims of this study were to describe the long-term outcomes after anti-TNF withdrawal and discover potential biomarkers to predict long-term remission as an approach to towards personalized medicine. Methods: 75 patients with moderate to severe UC treated to remission with anti-TNF were included in the study. These patients were categorized as either "Long term remission" (LTR) or "Relapse". The "Relapse" group were divided in subgroups by the highest treatment level needed to obtain remission the last 3 years of observation: non-biological therapy, biological therapy or colectomy. LTR were divided in LTR + immunomodulating (imids) drugs and a new clinical phenotype "Near the Cure of disease" (NCD), defined as > 3 years in remission with no medication or 5ASA only. Results: The median (IQR) observation time of all patients included were 121(111–137) months. Of the 75 patients 46 (61%) did not receive biological therapy including 23 (31%) in LTR + imids. Of the 23 patients 16 were defined as NCD with an observation time of median (IQR) 95(77–113) months. Fourteen patients underwent colectomy and 15 patients received biological therapy the last 3 years of the follow-up. Mucosal TNF copies/µg mRNA < 10 000 at anti-TNF discontinuation predicted long-term remission, biological free remission and lower risk of colectomy with a HR 0.36 (0.14–0.92) for long term remission, HR 0.17 (0.04–0.78) for biological free remission and HR 0.12 (0.01–0.91) for coelctomy. Conclusion: This 10-year anti-TNF discontinuation follow up study of UC shows that 61% of patients experience an altered phenotype to a milder disease course without need of biological therapy. Normalized mucosal TNF transcript predict this mild disease course and lower risk of colectomy. Of special interest is that 21% of the patients defined as "Near the cure of disease" were in long-term remission without any medication or receiving 5ASA only.